2015
DOI: 10.15740/has/eti/6.1/1-11
|View full text |Cite
|
Sign up to set email alerts
|

Design rainfall estimation using probabilistic approach for Adilabad district of Telangana

Abstract: This paper presents the estimation of design rainfall of Adilabad district at different probability levels. The 30 years monthly rainfall data of Adilabad district were analyzed by EasyFit software to identify the best fit probability distribution. Chisquare test is used as a goodness of fit criteria. It was found that general extreme value, Gamma distribution and Gumbel max were best fitted to monsoon (June-Sept.), post-monsoon (March-May) and pre-monsoon (Oct.-Feb.) season, respectively. The data was then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For Ethiopia, Gumbel's extreme value distribution is suggested to fit the annual extremes rainfall data (Gebremedhin, 2017) .According to the result obtained from evaluated distribution functions , GEV has better described the given data sets. It is also the known best fit distribution function and uses only for extreme events (peak rainfalls) (Waghaye et al, 2015). Most hydrological studies require short duration (sub-daily) of rainfall data but in developing countries like Ethiopia, such short duration data was not available.…”
Section: Computed Extreme Rainfall Quantiles (X Y )mentioning
confidence: 99%
See 1 more Smart Citation
“…For Ethiopia, Gumbel's extreme value distribution is suggested to fit the annual extremes rainfall data (Gebremedhin, 2017) .According to the result obtained from evaluated distribution functions , GEV has better described the given data sets. It is also the known best fit distribution function and uses only for extreme events (peak rainfalls) (Waghaye et al, 2015). Most hydrological studies require short duration (sub-daily) of rainfall data but in developing countries like Ethiopia, such short duration data was not available.…”
Section: Computed Extreme Rainfall Quantiles (X Y )mentioning
confidence: 99%
“…The first known problem in hydrology deals with interpreting past records of hydrological events in terms of future probabilities of occurrence. It can be solved by using frequency analysis (Waghaye et al,2015). Historic rainfall event statistics are used to predict extreme events and statistical distributions that can interpret the fitness of the data (Vucetic & Simonovic, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of computers has paved the way for present-day practitioners in using several software platforms to analyze the LOS datasets and fit the theoretical distributions. It is observed that studies considered so far used mainly rank-based approach for analyzing the datasets (Sastry and Sinha 2010;Sanjeev Kumar et al 2011;Waghaye et al 2015). However, such approach ranks a distribution inherently even if the test rejects the hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in Earth's climate system can disrupt the delicate balance of hydrologic cycle and can eventually lead to increased occurrence of extreme events (such as flood droughts, heat waves, summer, and ice storms, etc.) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing trend of rainfall extremes has quantifiable impacts on rainfall frequency relations and an increase in the intensity and frequency of extreme rainfall events may result in the flooding of urban areas [2].…”
Section: Introductionmentioning
confidence: 99%